Analisis pengaruh upah minimum provinsi, kemiskinan dan indeks pembangunan manusia terhadap tingkat partisipasi angkatan kerja di Provinsi Jambi - Faruq Kukuh Wasono; Erfit Erfit; Erni Achmad (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to analyze the development of labor force participation rate in Jambi province, minimum wages, poverty, and human development index in and to analyze the influence of minimum wage, poverty, and human development index on labor force participation rate in Jambi province from 2002 to 2017 using multiple linear regression tools and the analysis method used is a descriptive and quantitative analysis using secondary data. based on the results of the study showed the development of the provincial minimum wage has increased every year, while poverty, human development index, and labor force participation rate in Jambi province fluctuated from 2002 -2017. and based on the test results simultaneously the minimum wage province, human development index poverty has a significant effect on the level of labor participation in Jambi province, while the partial test results are known that the minimum wage variable of the human development index has a negative and significant effect on the labor force participation rate in Jambi province. Keywords : Labor for participation rate, provincial minimum wage, pover, Human development index